Motivational Factors as Predictors of Teaching Motivation Among Junior High School Teachers in the New Normal - Revilla, Emmanuel C.; Jr, Leandro R. Remojo; Borja, Joanna Marie A. de (Jurnal Pendidikan Progresif, 2022)
Do Health and Safety, Readiness and Preparedness, and Support and Opportunities Predict Teaching Motivation? Objectives: The study determined the relationship of three motivational factors (Health and Safety; Readiness and Preparedness in Distance Learning; and Support and Opportunities) to the teaching motivation in the new normal of junior high school teachers. Methods: Regression analysis was used to measure the significant relationships among the three motivational factors and teaching motivation of 204 (34% male and 66% female) respondents who answered the online survey. Findings: The motivational factors such as health and safety (????=0.258; p-value=0.003) and readiness and preparedness in distance learning (????=0.217; p-value=0.024) revealed that these are significant predictors of teaching motivation. Conclusion: Even though the three motivational factors have a direct positive relationship to teachers’ level of motivation, it was revealed that the health and safety motivational factors result in the highest need of emphasis to level up a teacher's motivation to continue teaching. Keywords: teaching motivation, teachers’ motivational factors, health and safety, distance learning, support and opportunities.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202208